Implicit leadership theory : perceived leadership traits and employee turnover - Prahalath, Viresh (My University, 2018)
Implicit leadership theories refer to the idealised, cognitive perceptions that individuals have of leaders. This paper sought to answer if a match and / or mismatch between these idealised perceptions and the perceptions that subordinates have of their current leaders may result in the intention of an employee to leave an organisation. The paper hypothesised that a mismatch between the idealised implicit leadership theories that respondents possessed and current leadership qualities of their manager would result in an intent to leave an organisation. To do this, it had to resolve the first research problem: of identifying differences between idealised qualities of leaders among subordinates and what they perceive as the current qualities of their leader as well as the second: seeing if this mismatch was related to an intent to leave. This research is important because it adds to the existing body of knowledge surrounding cognitive theories that influence leadership-subordinate relationships. It provides insight into what influences the costly phenomenon of employee turnover and includes a range of managerial implications that arise from implicit leadership theories, detailing avenues of mediation. It also provides an understanding into why some leaders are more effective than others, why some rise to power as opposed to others and what universal qualities followers require in their leaders. It also provides a way forward regarding the required competencies that can be focused upon during the training and development of future leaders. Research was conducted through online surveys which had five parts, the first two asked respondents to identify idealised perceptions of leaders and their perception of their current leaders respectively per a 21-item scale used by Epitropaki & Martin (2005) in a similar study. The next three parts of the survey measured an employee’s job dissatisfaction, intent to leave, as well as the ease of movement they possessed in finding another job. It was found that job dissatisfaction served as a mediating variable between a mismatch between implicit leadership theories and current leadership traits and an intent to leave. Prototypic traits regarding sensitivity (helpfulness, sincerity and being understanding) proved to be most sensitive to the level of job satisfaction an employee has as well as anti-prototypic traits of being manipulative and conceited. The implications of this study are far reaching. It suggests that if a leader does not match the implicit leadership theories present in an employee, job dissatisfaction can occur resulting in an intent to 6 leave an organisation. This cognitive process goes much deeper than what an employee considers as “good” or “bad” leaders which makes them want to stay or leave. The scope of the study also includes space for the unexpected like anti-prototypic leadership qualities that may influence an employee to stay within an organisation or vice versa.
MBA
Keywords: Labor turnover -- South Africa. Leadership -- South Africa.